PAK Dewasa Dalam Gereja Lokal - Hotniel Simanjuntak; Nursalina Sihombing; Jonatan Desvela Tambunan; Damayanti Nababan (Jurnal Euangelion, 2022)
Abstract: Adult Education (Andragogy) must be based on assumptions about self-concept, experience, readiness to learn, and learning orientation. Self-concept relates to the need for an understanding of adults who are psychologically mature. Biblically, education is an effort to develop the insight, abilities and life attitudes of students through the teaching and example of their educators, so that (the goal) becomes a person of faith, integrity, character like Jesus and able to use their faith in responding to life's challenges and being able to humanize each other with various lives. which has been given by God given to children since childhood and taught by people who have gifts, are able to teach and are real examples of life based on Bible values. Abstrak: Pendidikan Orang dewasa (Andragogy) harus didasari asumsi tentang konsep diri, pengalaman, kesiapan belajar, dan orientasi belajar. Konsep diri berkaitan dengan perlunya pemahaman terhadap diri orang dewasa yang sudah matang secara psikologis. Secara Alkitabiah pendidikan adalah usaha menumbuh kembangkan wawasan, kemampuan dan sikap hidup peserta didik melalui pengajaran dan teladan pendidiknya, agar (tujuannya) menjadi pribadi yang beriman, berintegritas, berwatak seperti Yesus dan mampu menggunakan imannya dalam menjawab tantangan hidup serta mampu memanusiakan sesamanya dengan berbagai kehidupan yang telah dikaruniakan Tuhan yang diberikan kepada anak-anak sejak kecil dan diajarkan oleh orang-orang yang mempunyai karunia, cakap mengajar dan keteladanan hidup yang nyata berdasarkan nilai-nilai Alkitab.